ClinGen Variant Curation Expert Panel experiences and standardized processes for disease and gene‐level specification of the ACMG/AMP guidelines for sequence variant interpretation. Issue 11 (11th October 2018) - Rivera‐Muñoz, Edgar A.; Milko, Laura V.; Harrison, Steven M.; Azzariti, Danielle R.; Kurtz, C. Lisa; Lee, Kristy; Mester, Jessica L.; Weaver, Meredith A.; Currey, Erin; Craigen, William; Eng, Charis; Funke, Birgit; et al.
Abstract: Genome‐scale sequencing creates vast amounts of genomic data, increasing the challenge of clinical sequence variant interpretation. The demand for high‐quality interpretation requires multiple specialties to join forces to accelerate the interpretation of sequence variant pathogenicity. With over 600 international members including clinicians, researchers, and laboratory diagnosticians, the Clinical Genome Resource (ClinGen), funded by the National Institutes of Health, is forming expert groups to systematically evaluate variants in clinically relevant genes. Here, we describe the first ClinGen variant curation expert panels (VCEPs), development of consistent and streamlined processes for establishing new VCEPs, and creation of standard operating procedures for VCEPs to define application of the ACMG/AMP guidelines for sequence variant interpretation in specific genes or diseases. Additionally, ClinGen has created user interfaces to enhance reliability of curation and a Sequence Variant Interpretation Working Group (SVI WG) to harmonize guideline specifications and ensure consistency between groups. The expansion of VCEPs represents the primary mechanism by which curation of a substantial fraction of genomic variants can be accelerated and ultimately undertaken systematically and comprehensively. We welcome groups to utilize our resources and become involved in our effort to create a publicly accessible, centralized resource for clinically relevant genes and variants. Abstract : ClinGen is organizing Variant Curation Expert Panels (VCEPs) to develop specifications to the ACMG/AMP guidelines for genes or diseases of interest, interpret variants according to these guidelines, and publish the expert interpretations through the publicly available ClinVar database. A stepwise process was iteratively developed for ClinGen VCEPs to apply to submit variant assertions to ClinVar at the Expert Panel level of review. Other groups that wish to assemble as VCEPs are encouraged, though not required, to follow these steps.